DIAGNOSTICS OF TRIPANОSOMOSIS OF CAMELS AND CONDUCT OF EPISATOLOGICAL MONITORING IN TURKESTAN REGION - Baizhanov, K.S.; Kuzerbayeva, A. T.; Zhanbyrbayev, M.; Ospanova, M. S.; Yermekbaeva, R. Zh. (Жәңгір хан атындағы БҚАТУ, 2024)
The article discusses a study conducted in the Turkestan region focusing on camel trypanasomiasis. This study utilized serological tests with antigens derived from a local strain to enhance disease detection. Trypanasomiasis is not only a concern for camels but also affects horses, donkeys, and various laboratory animals like dogs, rabbits, guinea pigs, and white mice. This waterborne disease is prevalent in Central Asian republics and Kazakhstan, particularly in areas around the Turkestan, Kyzylorda, Atyrau regions, and along the Ural and Syrdarya rivers. Insects such as flies and mosquitoes are known carriers of this disease, which is typically transmitted through vector-borne routes. The incidence of the disease tends to spike in autumn, with covertly infected animals often being the primary source of new infections. Given the serious implications of the disease, it's crucial to regularly monitor camel populations in affected areas for early detection and prevention of widespread outbreaks. The use of antigenic preparations from local parasite strains has been highlighted as critical for the rapid diagnosis of trypanasomiasis. Additionally, to safeguard livestock, it is recommended to utilize pastures that are distant from mosquito breeding grounds. In light of these challenges, there is an increased emphasis on developing camel farming in the Turkestan region. This development aims to maximize the production of camel products, including meat and fur. However, to successfully expand camel numbers, it is essential to ensure they are healthy and free from diseases like invasive trypanasomiasis.
Diagnostics of tripanоsomosis of camels and conduct of episatological monitoring in turkestan region / K.S. Baizhanov, A. T. Kuzerbayeva, M. Zhanbyrbayev, M. S. Ospanova, R. Zh. Yermekbaeva . - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 1-1 (74). Ч. І. - Р. 67-76.
Keywords: Immune Reactor; Carrier-transmitted; Dromedary; Strain; Sleeping Sickness; Pervasive; зкату; научный журнал